Meta-Analysis: The Effect of Anemia in Pregnant Women on the Risk of Postpartum Bleeding and Low Birth Weight - Adhimukti, Fahmi; Budihastuti, Uki Retno; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Anemia in pregnancy usually occurs in the 1st and 3rd trimesters with Hb levels below 11g% and in the 2nd trimester with Hb levels less than 10.5g%. The prevalence of anemia in pregnant women around the world ranges from 41.8% to 43.8%, which means that around 56-59 million pregnant women suffer from anemia. Factors that cause anemia that often appear in pregnant women are malnutrition and iron deficiency, so that iron anemia in pregnancy can result in increased maternal mortality rates (MMR). Anemia during pregnancy can result in fetal death, abortion, birth defects, low birth weight and can cause bleeding during labour.Subjects and Method: Meta-analysis was carried out using the PRISMA flowchart and the PICO model (Population: pregnant women, Intervention: anemia, Comparison: no anemia, Outcome: LBW and postpartum hemorrhage). The databases used are PubMed, Research Gate, Science Direct, and Google Scholar with the keywords